Changes in unsaturated fatty acids in milk under vegetative regulation in dairy cattle - O. Zhurenko; I. Hryshchuk; D. Kryvoruchko; V. Zhurenko (Тваринництво та технології харчових продуктів, 2024)
The fatty acid content of milk serves as a reliable indicator of its quality. Changes in this parameter depend on various factors, which must be considered when implementing methods to adjust the fatty acid composition of milk. This study aimed to determine the influence of the autonomic nervous system in dairy cows on the fatty acid composition of milk. The research was conducted on Ukrainian Black-and-White dairy cows. Experimental groups were formed using electrocardiography to establish the tone of the autonomic nervous system. Fatty acid analysis was performed via gas chromatography, with lipid extraction conducted using the Folch method. It was observed that the proportion of myristoleic acid in the experimental group of vagotonic cows was 6.9% higher than that of normotonic cows (P < 0.05). The content of palmitoleic acid in the milk of vagotonic cows, according to chromatographic analysis, was 11.6% higher (P < 0.01) and in sympathotonic cows 5.8% higher (P < 0.05) compared to normotonic cows. The oleic acid content in the milk of vagotonic cows was 4.2% higher (P < 0.01) and in sympathotonic cows 1% higher (P < 0.05) compared to normotonic cows. The linoleic acid content in the milk of vagotonic cows was 6.1% higher (P < 0.001) and in sympathotonic cows 31.7% higher (P < 0.001) than that of normotonic cows. Conversely, the α-linolenic acid content in vagotonic cows was 38.5% lower (P < 0.01) and in sympathotonic cows 34.6% lower (P < 0.01) than in normotonic cows. These findings indicated that the experimental group of normotonic cows had the lowest levels of unsaturated fatty acids in milk